KLIKK proteases of Tannerella forsythia: putative virulence factors with a unique domain structure - Ksiazek, Miroslaw; Mizgalska, Danuta; Eick, Sigrum; Thøgersen, Ida B.; Enghild, Jan J.; Potempa, Jan (Frontiers in Microbiology, 2015)
Comparative genomics of virulent Tannerella forsythia ATCC 43037 and a close health-associated relative, Tannerella BU063, revealed, in the latter, the absence of an entire array of genes encoding putative secretory proteases that possess a nearly identical C-terminal domain (CTD) that ends with a -Lys-Leu-Ile-Lys-Lys motif. This observation suggests that these proteins, referred to as KLIKK proteases, may function as virulence factors. Re-sequencing of the loci of the KLIKK proteases found only six genes grouped in two clusters. All six genes were expressed by T. forsythia in routine culture conditions, although at different levels. More importantly, a transcript of each gene was detected in gingival crevicular fluid (GCF) from periodontitis sites infected with T. forsythia indicating that the proteases are expressed in vivo. In each protein, a protease domain was flanked by a unique N-terminal profragment and a C-terminal extension ending with the CTD. Partially purified recombinant proteases showed variable levels of proteolytic activity in zymography gels and toward protein substrates, including collagen, gelatin, elastin, and casein. Taken together, these results indicate that the pathogenic strain of T. forsythia secretes active proteases capable of degrading an array of host proteins, which likely represents an important pathogenic feature of this bacterium.